Seasonal abundance and host plants of coconut stick insect (Graeffea crouanii Le Guillou) in coconut plantations of Fiji islands - Deesh, Aradhana D.; Jokhan, Anjeela D.; Joshi, Ravindra C.; Khan, Mohammed M.G.; Jerard, B. Augustine (Journal of Plantation Crops, 2020)
Field survey conducted in major coconut growing regions in the three Fiji islands viz., Viti Levu, Vanua Levu, and Taveuni, revealed the presence of only one pest species of stick insect, Graeffea crouanii. Temperature had a significant effect on the level of infestation in the farms surveyed, while the effect of rainfall and humidity on the infestation was insignificant. Severe infestation was observed in isolated pockets, and the pest distribution was discontinuous in the surveyed areas. On a damage scale index, the insect infestation on coconut palms ranged from 0 to 4 grades. The peak increase of G. crouanii populations was from November to April in wet season at each of the three hotspots: Namaumada (Viti Levu), Dawara (Vanua Levu), and Salialevu (Taveuni). The occurrence of G. crouanii at varying damage levels in the present study may be attributed to the presence of sparse coconut palms in isolated coconut plantations. The field survey identified many alternate host plants of G. crouanii in the two plant families viz., Arecaceae and Pandanaceae. The information on the seasonal abundance and infestation levels of G. crouanii and its alternate host plants are discussed in formulating location-specific pest management strategies.